Plyometric training - A boom to badminton player`s agility - Mathachan, E. (Journal of The Gujarat Research Society, 2019)
The aim of the paper is to co-relate the effect of plyometric training on agility in badminton players and include the same into their training. Apparently no study or limited study has been done to examine the effect of plyometric training on the agility of badminton players. Selected agility test were taken into consideration to relate the performance factors. The plyometric training introduced to the subjects is purely and functionally designed with that of movements specific to badminton. This study shows that due to the plyometric training there is a improvement in Agility. Motion analysis of a typical badminton match reveals that there are many changes in direction and it requires the athlete to be very agile in all directions. It is concluded with reference from the available articles and research studies that due to plyometric training there will be improvement in agility among badminton Players. PRACTICAL APLICATION: Coaches should consider implementing a modified plyometric training program for the development of agility in their athletes.